Syi’îr Ngudi Susilo as Social Capital in The Glocalization of Javanese-Islamic Moral Education - Asrori, Muhammad; Ahadiyah, Wahyuni; Albab, Ulil (Proceedings of Annual Conference for Muslim Scholars, 2025)
This article examines Syi'îr Ngudi Susilo as a cultural text containing Javanese-Islamic moral values and its role in the glocalization of Islamic character education. Using Paul Ricoeur’s hermeneutic method—naïve reading, structural analysis, and critical interpretation—the study reveals ethical values such as humility, manners, prayer discipline, Qur’an recitation, and respect for teachers as a synthesis of Javanese and Islamic teachings. These values form social capital through shared norms, beliefs, and networks in Javanese Muslim communities. Syi'îr Ngudi Susilo illustrates the integration of universal Islamic norms into local Javanese traditions, showing how character education is localized yet remains globally relevant. As traditional literature, it serves as a cultural medium of moral education while transmitting modern Islamic ideals in a local (Javanese-speaking) context. Through this synthesis, the syi’ir strengthens social capital and ensures the continuity of Javanese-Islamic moral teachings for younger generations.